Modifiable socio-cultural beliefs and practices influencing early and adequate utilisation of antenatal care in rural Bangladesh: A qualitative study. (February 2021) - Nisha, Monjura Khatun; Alam, Ashraful; Rahman, Aminur; Raynes-Greenow, Camille
Abstract: Objective: Our objective was to explore the socio-cultural factors that influence women's early and adequate utilisation of antenatal care (ANC) in rural Bangladesh. Methods: A qualitative study was conducted in two rural settings of Bangladesh, including 32 in-depth interviews with pregnant or recently delivered women, husbands whose wives were pregnant or had a recent birth, mothers-in-law whose daughters-in-law were pregnant or had a recent birth; 2 focus group discussions with husbands; and 4 key-informant interviews with community health workers. We used thematic analysis to analyse the data. Findings: ANC initiation in the first trimester was not a priority for most women. Women's lack of awareness about the appropriate timing of the first ANC contact, lack of decision-making autonomy and fear of caesarean section were the major barriers to the early and adequate ANC utilisation. There were many superstitions around pregnancy in rural settings which prevented women seeking early and adequate antenatal care and led them to seek care from traditional care providers instead of formal care providers. Conclusion: ANC utilisation in rural Bangladesh was associated with several socio-cultural beliefs which are modifiable with interventions that have been used in similar settings. Targeting these socio-cultural barriers with context- and community-specific interventions is important to improve overall ANC utilisation at the community-level which can lead to significant improvements in perinatal outcomes.